The Effects of Interaction between Internal Auditor and Audit Committee on Fraud Detection in Malaysia - Lylia Hamdan, Sunita; Jaffar, Nahariah; Ab Razak, Ruzanna (International Journal of Engineering and Technology, 2018)
This study aims to examine the effect of interaction between internal auditor and audit committee on fraud detection in Malaysia.  Specific interaction is firstly; audit committee approving the appointment of chief audit executive, the evaluation of chief audit executive, the dismissal of chief audit executive, the internal audit budget and the internal audit plan or program.  Secondly, audit committee’s involvement in reviewing internal auditor’s work specifically; providing input for the internal audit plan, reviewing the results of internal auditing related to financial reporting, reviewing the results of internal auditing related to internal control, reviewing the results of internal auditing related to compliance with laws and regulation, reviewing the internal audit involvement in management responses to internal audit suggestions, reviewing the difficulties or scope restrictions encountered by internal auditors and reviewing the coordination between internal auditors and external auditors.  Survey questionnaires were mailed to internal auditors attached to 782 companies listed on Bursa Malaysia’s main market. The results of this study suggest that involvement of audit committee in approving chief audit executives’ matters is insignificant on internal auditors’ contribution to fraud detection.  However, audit committee’s involvement in reviewing internal auditors’ work significantly influence the internal auditors’ contribution in fraud detection.
Keywords: internal auditor; audit committee; fraud detection